Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
[tex] (\frac{1}{3} x-11)^{ \frac{1}{2} }=5\\ ((\frac{1}{3} x-11)^{ \frac{1}{2} })^{2}=(5)^{2}\\ \frac{1}{3} x-11=25\\ \frac{1}{3} x=36\\x=108[/tex]
square both sides to get
(1/3x-11)=25
1/3x-11=25 then solve
why? because ^(1/2) means "take the square root". We need to "undo", or find the inverse so we square both sides.
(1/3x-11)=25
1/3x-11=25 then solve
why? because ^(1/2) means "take the square root". We need to "undo", or find the inverse so we square both sides.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.